Application of Cognitivism Theory in Islamic Education Learning for Grade V Students - Milda, Jefpi; Putri, Umi Amelia; Harto, Kasinyo; Suryana, Ermis (FKIP - Universitas Riau, 2025)
This study aims to analyze the application of cognitivism theory in learning Islamic Religious Education (PAI) for fifth grade students of SDN 124 Palembang and evaluate its impact on improving conceptual understanding and internalization of religious values. The theory of cognitivism, which emphasizes the mental process of understanding, storing, and integrating new information, is used as the main theoretical framework in developing learning strategies. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results showed that the application of cognitivism-based learning strategies-such as elaboration of meaning, linking new concepts with students' experiences, and the use of visual media-contributed significantly to improving the understanding of PAI materials. In addition, this approach also encouraged students' active participation in reflective discussions and the strengthening of religious values in daily life. The findings indicate that the cognitivism approach can be an effective pedagogical alternative in learning PAI at the elementary school level. The implications of this study open up space for the development of learning models that are more contextual and oriented to students' thinking processes.